2010
DOI: 10.1002/pbc.22714
|View full text |Cite
|
Sign up to set email alerts
|

Delay and causes of delay in the diagnosis of childhood cancer in Africa

Abstract: There is considerable delay in diagnosing childhood cancer in the area served by Tygerberg Hospital, due mostly to a physician delay of 20 days on average. The findings of our unit should be correlated with other South African centers. There is a clear need to increase parental awareness of childhood cancer and to intensify the education of nurses and doctors with regard to the warning signs of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
118
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(152 citation statements)
references
References 9 publications
21
118
11
Order By: Relevance
“…The short total delay reported from South-Africa could be a reflection of the superior infrastructure and health-care system in the country and is similar to total delays found in high-income countries, such as Canada which also has a median total delay of 34 days. [15][16][17][18] Health-care system delay in our study was significantly longer than patient delay. This is unlike what has been reported by the Nigerian study where patient delay was longer than health-care system delay as well as the Burkitt lymphoma study in Western Kenya.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The short total delay reported from South-Africa could be a reflection of the superior infrastructure and health-care system in the country and is similar to total delays found in high-income countries, such as Canada which also has a median total delay of 34 days. [15][16][17][18] Health-care system delay in our study was significantly longer than patient delay. This is unlike what has been reported by the Nigerian study where patient delay was longer than health-care system delay as well as the Burkitt lymphoma study in Western Kenya.…”
Section: Discussionmentioning
confidence: 56%
“…Although the total delay figures are similar to findings in Nigeria where median total delay was 109 days, our figures are longer than what has been reported in other studies done in Africa. [15][16][17][18] A study done in Western Kenya and Uganda, specifically looking at Burkitt lymphoma, reported total delays of 12.1 and 12.9 weeks respectively. This is shorter than what we found though close to what we found in our Non-Hodgkin lymphoma patients who had a mean total delay of 73 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study in the Tygerberg Hospital referral area showed that a considerable delay in diagnosis could be attributed to physicians making a wrong initial diagnosis, delay in performing clinical tests, and delay in obtaining histopathological results. [14] Children in lower socioeconomic areas have less access to care than those in higher-income groups. Awareness campaigns in SA can improve knowledge about child hood malignancies and facilitate early diagnosis, particularly among these underprivileged children.…”
Section: Discussionmentioning
confidence: 99%